STRATEGY FOR MAINTAINING THE EXISTENCE OF THE FARISA CRAFT BUSINESS IN DUKUH VILLAGE, GONDANG DISTRICT, TULUNGAGUNG DISTRICT - Dewi, Rohma Aliska; Suryaningsih, Tutut (Jurnal Ekonomi dan Pendidikan, 2023)
Responding to the increasingly stringent developments in the business world, entrepreneurs must plan the right strategy so that their business continues to exist. The purpose of this research is to find out how the strategy of the "Farisa Craft" business owner is in maintaining the existence of his business. This type of research is descriptive qualitative with data collection techniques of observation, interviews, FGD and documentation. The results showed that the strategies used by Farisa Craft to survive were marketing strategies, product innovation and branding. In product innovation, farisa created 5 new variations of the coconut coir pot model, one of which is kokedama. In the marketing strategy, the potential targets targeted by farisa craft are the flower lover community and civil servants. One of the Farisa Craft promotions is Sales Promotion. Meanwhile branding is done by making marketing videos, endorsements, maintaining product and service quality.